2010
DOI: 10.1210/jc.2009-2668
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Insulin-Like Growth Factor-Binding Protein-2 Levels as Diagnostic and Prognostic Biomarker of Colorectal Cancer

Abstract: IGFBP-2 is a potential diagnostic and prognostic biomarker of CRC. LOI of IGF-II is significantly associated with poor prognosis in patients with stage IV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 45 publications
3
48
0
Order By: Relevance
“…24 In addition, increased levels of IGFBP-2 in the serum of cancer patients was shown in a variety of human cancers to be an indication of poor prognosis, [25][26][27][28][29] including CRC patients. [30][31][32][33] A recent study identified IGFBP-2 signaling as an important factor in the recruitment of endothelial cells in metastatic breast cancer by a miR-126-dependent mechanism. 34 By chromatin immunoprecipitation and gene promoter reporter activation we showed that IGFBP-2 transactivation is enhanced by NF-kB, in agreement with the increase in IGFBP-2 protein levels in p65-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, increased levels of IGFBP-2 in the serum of cancer patients was shown in a variety of human cancers to be an indication of poor prognosis, [25][26][27][28][29] including CRC patients. [30][31][32][33] A recent study identified IGFBP-2 signaling as an important factor in the recruitment of endothelial cells in metastatic breast cancer by a miR-126-dependent mechanism. 34 By chromatin immunoprecipitation and gene promoter reporter activation we showed that IGFBP-2 transactivation is enhanced by NF-kB, in agreement with the increase in IGFBP-2 protein levels in p65-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, causality cannot be ascertained in this cross-sectional study. Whether hyperglycemia is, in effect, a proxy of more fundamental metabolic derangement that more directly leads to neogrowth of colorectal epithelium is certainly interesting [34] and deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of GH (13), IGFs and IGFBPs (14)(15)(16) are often taken into consideration as prognostic biomarkers in critically ill patients. Lower levels of IGF-I and IGFBP-3 and higher levels of GH, IGFBP-1 and IGFBP-2 are found in non-survivors compared with survivors.…”
Section: Discussionmentioning
confidence: 99%